1989
DOI: 10.1055/s-2007-1009283
|View full text |Cite
|
Sign up to set email alerts
|

Flight Effects on Plasma Levels of Lipid, Glucagon and Thyroid Hormones in Homing Pigeons

Abstract: Significant increases in the concentration of plasma glucagon-like immunoreactivity (GLI) and plasma levels of free fatty acids (FFA) and triglycerides (TG) concomitant with decreases in circulating levels of thyroxine (T4) and triiodothyronine (T3) and T3/T4 ratio were observed in homing pigeons, untrained for 3 months, after a flight of 48 km lasting 90-160 min. The increased level of FFA is attributed to glucagon stimulated lipolysis. The elevation of TG levels may be due to altered partitioning and utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Glucagon. Plasma glucagon concentration was measured by radio immunoassay (Linco Research), as previously described (4,18). The sensitivity of the assay was 20 pg/ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucagon. Plasma glucagon concentration was measured by radio immunoassay (Linco Research), as previously described (4,18). The sensitivity of the assay was 20 pg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity of the assay was 20 pg/ml. Because the primary antibody is directed at a mammalian glucagon molecule, the values are expressed as glucagon-like immunoreactivity for avian plasma, as previously described (4,18).…”
Section: Methodsmentioning
confidence: 99%
“…It is now well established that during sus tained muscular activity, birds metabolize fat as the chief fuel [49][50][51][52][53], Marked increases in postflight plasma levels of triglycerides, free fatty acids (FFA), glucagon and growth hor mone (GH) have been reported in homing pigeons [23,54], Increases in plasma levels of FFA and GH have also been shown in pigeons subjected to heat stress and dehydration [55], The observation that plasma levels of AVT are increased in heat-stressed domestic fowl [ 14] suggests that AVT may have a lipolytic action besides its well-known role as an anti diuretic hormone. That AVT has indeed an adipokinetic action has been demonstrated in pigeon in vivo and also in in vitro experi ments [56] using pigeon adipose tissue slices [57], an action that may be mediated by cAMP [58], In this context, it may be men tioned that the release of AVT from the poste rior lobe in migratory birds prior to migration has been considered as an important event in the initiation of Spring migratory activity [59].…”
Section: Discussionmentioning
confidence: 99%
“…Trained homing pigeons are an excellent experimental material for studies on the ef fects of natural free flight on the physiology of bird flight. Recent studies with homing pi geons have thrown considerable new light on the effects of flight on circulating levels of metabolites and certain hormones involved in metabolic regulation [21][22][23], In the present study, we have investigated possible changes in circulating levels of AVT and MT as a result of flight in homing pigeons.…”
Section: Introductionmentioning
confidence: 99%
“…The role of other hormones in the regulation of flight metabolism has been investigated in free-flying homing pigeons but not in migrant birds. After a flight of 48 km or about 1.5 h, significant increases of glucagon, adrenaline, noradrenaline, and growth hormone and either significantly reduced or unchanged concentrations of T3 and T4 were found (George et al 1989;John et al 1988;Viswanathan et al 1987). George et al (1989) concluded that increased sympathetic activity increases glucagon, a lipid-mobilizing hormone.…”
Section: Hormonal Regulation Of Flight Metabolismmentioning
confidence: 96%